2000
DOI: 10.1021/jf000912k
|View full text |Cite
|
Sign up to set email alerts
|

Water Stress and Accumulation of β-N-Oxalyl-l-α,β-diaminopropionic Acid in Grass Pea (Lathyrus sativus)

Abstract: Grass pea seedlings were grown in an irrigated field. Roots of 15-day-old seedlings were treated with PEG, and leaves were studied. With the duration of PEG treatment, changes in the lipid peroxidation and activities of superoxide dismutase, catalase, peroxidase, and glutathione reductase as well as contents of hydrogen peroxide and beta-N-oxalyl-L-alpha,beta-diaminopropionic acid (ODAP) were assayed. The results indicate that with the duration of PEG treatment, activities of superoxide dismutase, peroxidase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 25 publications
3
30
0
Order By: Relevance
“…Previous studies have shown that the concentration of b-ODAP increased in grass pea seeds exposed to drought (Hussain et al 1997;Yan et al 2006), and the increase in the b-ODAP concentration in various tissues of grass pea has been considered an important physiological response to drought stress (Xing et al 2001;Zhou et al 2001;Haque et al 2011). Other studies have shown that water shortage significantly reduced biomass and seed yield of grass pea compared with a well-watered control, but had no effect on b-ODAP concentration in seeds, resulting in much less accumulation of b-ODAP in water-stressed grass pea (Gusmao et al 2012;Kong et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the concentration of b-ODAP increased in grass pea seeds exposed to drought (Hussain et al 1997;Yan et al 2006), and the increase in the b-ODAP concentration in various tissues of grass pea has been considered an important physiological response to drought stress (Xing et al 2001;Zhou et al 2001;Haque et al 2011). Other studies have shown that water shortage significantly reduced biomass and seed yield of grass pea compared with a well-watered control, but had no effect on b-ODAP concentration in seeds, resulting in much less accumulation of b-ODAP in water-stressed grass pea (Gusmao et al 2012;Kong et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Grass pea (Lathyrus sativus, Fabaceae) is a crop highly tolerant to the stress caused by various abiotic factors (Vaz Patto et al 2006). Even though the exact mechanism of this tolerance is still not known, there are reports indicating that it can rely on the ability to adjust the plants osmotic potential (Jiang et al 2013;Piwowarczyk et al 2014), elevated antioxidant enzyme activity (Jiang et al 2013), accumulation of polyamines and b-N-oxalyl-L-a,b-diaminopropionic acid (Xing et al 2001;Xiong et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The typical profile of fatty acids in a maize kernel is composed of 57.9% linoleic acid, <1% linolenic acid, 25.2% oleic acid, 11.6% palmitic acid and 1.8% stearic acid (White et al, 2003;Ashgan Abou Gabal and Amera Zaitoun, 2015). In earlier studies it has been reported that water shortage, along with N application at low or high doses can affect the chemical composition of different seeds by different metabolic processes (El-Deen et al, 1997, Yang et al, 2004, Xing et al, 2001Pavlista et al, 2016a, Pavlista et al, 2016b. However, the effects of fertilizer and water shortage on the fatty acid composition of maize oil have been poorly investigated.…”
Section: Introductionmentioning
confidence: 99%